The tau code - Avila, Jesus (Frontiers in Aging Neuroscience, 2009)
In this short review, I will focus on how a unique tau gene may produce many tau isoforms through alternative splicing and how the phosphorylation of these isoforms by different kinases may affect their activity and behaviour. Indeed, each of the different tau isoforms may play a distinct role under both physiological and pathological conditions. Thus, I will discuss whether a tau code exists that might explain the involvement of different tau isoforms in different cellular functions.